The Role of Toll-Like Receptor-2 in the Pathogenesis of Pulmonary Tuberculosis - Sudarto Sudarto; Zen Hafy; Irsan Saleh; Iche Andriyani Liberty; Zen Ahmad; Fadhyl Zuhry Lubis; Owen Hu; Welly Salutondok (GLOBAL HEALTH SCIENCE GROUP, 2025)
Pulmonary tuberculosis (PTB), primarily caused by Mycobacterium tuberculosis (M.tb), remains a major global health burden. Toll-like receptor 2 (TLR-2), a critical component of the innate immune system, plays a key role in the host-pathogen interaction by recognizing specific components of the mycobacterial cell wall and initiating downstream inflammatory pathways. However, the dual role of TLR-2 in both protective immunity and immune evasion by M.tb contributes to the complexity of TB pathogenesis. This study aims to investigate the role of Toll-Like Receptor-2 (TLR-2) in the pathogenesis of pulmonary tuberculosis, including its immunological mechanisms, relationships with disease severity, and the potential of TLR-2 as a diagnostic and therapeutic target. This literature review systematically analyzed molecular mechanisms involving TLR-2 signaling in pulmonary TB using peer-reviewed primary and secondary sources from experimental and clinical studies. Emphasis was placed on signal transduction (NF-κB and MAPK), cytokine profiles, antigen presentation, and the impact of TLR-2 gene polymorphisms on TB susceptibility. Activation of TLR-2 through ligands such as lipoproteins, lipoarabinomannan (LAM), and PE/PPE proteins initiates immune responses via MyD88-dependent pathways, leading to the release of proinflammatory cytokines (TNF-α, IL-6, IL-12). TLR-2 also enhances the function of macrophages and dendritic cells, promoting Th1-mediated immunity. However, chronic or excessive stimulation of TLR-2 can suppress antigen processing, promote IL-10 expression, inhibit phagolysosome fusion, and facilitate M. tb survival within host macrophages. Polymorphisms in the TLR-2 gene (e.g., rs3804099) have been associated with increased susceptibility and variable clinical outcomes in PTB. TLR-2 plays a paradoxical role in pulmonary tuberculosis by mediating both protective immunity and facilitating immune evasion by M.tb. Understanding the balance of TLR-2 signaling and genetic variation is crucial for developing immunomodulatory therapies and personalized interventions in TB management.